2016
DOI: 10.1515/folmed-2016-0039
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Role of Adiponectin, Leptin and Asymmetric Dimethylarginine in the Process of Atherosclerosis

Abstract: Adipose tissue is recognized as a rich source of proinflammatory mediators that may directly contribute to vascular injury, insulin resistance, and atherogenesis. Many studies have shown that adiponectin has antiatherogenic and anti-inflammatory properties. Adiponectin acts not only as a factor increasing insulin sensitivity, and the protective effect may result from its ability to suppress production of proinflammatory cytokines. It negatively regulates the expression of TNF-alpha and C-reactive protein (CRP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
0
10
0
2
Order By: Relevance
“…These proteins are known under the term “adipokines,” for example, adiponectin, leptin, resistant, visfatin, retinol‐binding protein 4, etc., which are involved in the pathophysiology of obesity and insulin resistance and therefore have indirect effects on atherosclerosis . For instance, adiponectin is an adipose tissue‐derived adipokine which has protective role in the initiation and progression of atherosclerosis through its anti‐inflammatory and antiatherogenic effects . Leptin exerts various atherogenic effects such as induction of endothelial dysfunction, stimulation of inflammatory reaction and oxidative stress, decrease in paraoxonase activity, platelet aggregation, etc .…”
Section: Introductionmentioning
confidence: 99%
“…These proteins are known under the term “adipokines,” for example, adiponectin, leptin, resistant, visfatin, retinol‐binding protein 4, etc., which are involved in the pathophysiology of obesity and insulin resistance and therefore have indirect effects on atherosclerosis . For instance, adiponectin is an adipose tissue‐derived adipokine which has protective role in the initiation and progression of atherosclerosis through its anti‐inflammatory and antiatherogenic effects . Leptin exerts various atherogenic effects such as induction of endothelial dysfunction, stimulation of inflammatory reaction and oxidative stress, decrease in paraoxonase activity, platelet aggregation, etc .…”
Section: Introductionmentioning
confidence: 99%
“…NO is mainly catalyzed and produced by eNOS, which has the function of vasodilatation and protecting vascular endothelium under physiological contents [ 25 , 26 ]. Accumulating evidence has suggested that intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule 1 (VCAM-1), endothelin 1 (ET-1), and E-selectin play pivotal roles in the mechanisms of endothelial dysfunction [ 27 , 28 ]. In the present study, the expression of ICAM-1, VCAM-1, ET-1, and E-selectin was upregulated and the levels of NO and eNOS were downregulated in HUVECs cultured with culture medium of hypoxic JEG-3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reviewed by us and by others, atherosclerosis consists of an inflammatory response of arterial wall to injuries. This inflammation is often initiated by endothelial dysfunction and progresses to cellular adhesion molecules (CAM) expression, adhesion of circulating leukocytes to the endothelial cells (Koleva et al, 2016), leucocyte migration and the formation of a fibrous cap around a lipidic core, which compromises vascular lumen (Freitas-Lima et al, 2015). In addition to its traditional role in hypertension, the long-term blood pressure control system (the renin-angiotensin system -RAS) is directly involved in the development of atherosclerotic lesions due to its mainly effects on endothelial function, inflammation, fibrosis, coagulation balance, plaque stability, and structural remodeling (Montezano et al, 2014;Husain et al, 2015).…”
Section: Introductionmentioning
confidence: 99%